Word events perspectives on verbal notation - Lely, John 1976-; Saunders, James 1972- (Continuum, 2012)
"Verbal notation has emerged since the 1950s as a prominent medium in the field of experimental music, as well as in related areas of arts practice involving performance and object making ... This book examines the use of English grammar in verbal notation, with numerous examples of usage from specific verbal scores. Commentaries explore the compositional strategies and performance practice of particular works in key essays ... from composers, artists and performers"--P. 4 of cover
Includes bibliographical references (p. [440]-447) and index
Grammar -- Scores, writings and commentaries. Eric Andersen -- Robert Ashley -- G. Douglas Barrett -- Antoine Beuger -- George Brecht -- Gavin Bryars -- Arthur Bull -- John Cage -- Cornelius Cardew -- Tony Conrad -- Philip Corner -- Bill Drummond -- Ken Friedman -- Malcolm Goldstein -- Daniel Goode -- Lawrence Halprin -- Tom Johnson -- Seth Kim-Cohen -- Bengt af Klintberg -- Alison Knowles -- Takehisa Kosugi -- Joseph Kudirka -- Sol LeWitt -- Annea Lockwood -- Alvin Lucier -- George Maciunas -- Benedict Mason -- Kenneth Maue -- Max Neuhaus -- Pauline Oliveros -- Yoko Ono -- Michael Parsons -- Ben Patterson -- Michael Pisaro -- Erik Satie -- Craig Shepard -- Kunsu Shim -- Mieko (Chieko) Shiomi -- Hugh Shrapnel -- Howard Skempton -- Mark So -- Karlhainz Stockhausen -- Jennifer Walshe -- Manfred Werder -- John White -- Michael Winter -- Daniel James Wolf -- Christian Wolff -- Amnon Wolman -- La Monte Young
Keywords: Geschichte 1950-2012; Musical notation; Avant-garde (Music) / Notation; Englisch; Komposition -- Musik; Notenschrift; Experimentelle Musik; Wort -- Motiv; Aufsatzsammlung